Haemodynamic impacts of myocardial bridge length: A congenital heart disease. (July 2019) - Javadzadegan, Ashkan; Moshfegh, Abouzar; Mohammadi, Maryam; Askarian, Mahsa; Mohammadi, Mahsa
Highlights: For the 1st time ever, developing the model for and simulating the haemodynamics in a novel category of coronary artery disease named "myocardial bridge". Performing a cohort-based study ( n  = 10) to show significance of findings across the cohort. Using real patients' medical scans for reconstruction of anatomical models. Reconstructing 3D arterial geometry by fusing angiograms and intravascular ultrasound via an in-house technique. Using a sophisticated dynamic computational fluid dynamics (CFD) model to mimic realistic muscle contraction on the artery during cardiac motion. Using patient-specific boundary conditions and cardiac timings for CFD analysis. Abstract: Objectives: There is an association between long and thick myocardial bridging (MB), haemodynamic perturbations and increased risk of myocardial infarction. This study aims to investigate the alteration in coronary haemodynamics with increasing the length of MB. Methods: Angiography and intravascular ultrasound were performed in 10 patients with varying length of MB in the left anterior descending (LAD) artery. In silico models of MB were developed based on the reconstructed three-dimensional model of the LAD. The entire LAD was divided into 3 segments, proximal (pre-bridge), bridge and distal (post-bridge). Transient computational fluid dynamics simulations were performed to derive distribution of blood residence time and wall shear stress (WSS) over entire vessel including proximal, bridge and distal segments. Results: With increasing the length of MB, a decreasing trend was observed in the WSS over proximal segment whereas an increasing trend was found in the WSS over bridge segment. When patients were divided into 2 groups based on the average length of MB in the whole cohort (Lave  = 23.92 mm), patients with bridges longer than Lave had smaller WSS and higher residence time in the proximal segment compared to those with bridges shorter than Lave (0.59 ± 0.31 vs 0.21 ± 0.14 Pa and 0.0021 ± 0.0015 vs 0.0045 ± 0.0021 s). In contrast, patients with bridges longer than Lave had greater WSS in the bridge segment compared to those with bridges shorter than Lave (1.37 ± 1.66 vs 2.53 ± 3.14 Pa). No significant difference was found in the distal WSS of patients with short and long bridges. Conclusion: Our findings revealed a direct relationship between the length of MB and haemodynamic perturbations in the proximal segment such that the increased length of MB is associated with decreased WSS and increased residence time.